Versorgung von minderjährigen Flüchtlingen: Schwerpunkt Diagnostik und Prävention von Infektionskrankheiten = Care of child and adolescent refugees : focus on diagnosis and prevention of infectious diseases - Kobbe, Robin; Pfeil, Johannes (Notfall & Rettungsmedizin, 2016)
BackgroundChild and adolescent refugees in Germany represent a particularly vulnerable social group, and treating infectious diseases is a crucial part of providing for their medical care. From an infectious diseases perspective, refugees themselves, as a result of their difficult life situations, are the ones at highest risk. Even in crisis situations, medical practitioners are medically and ethically obliged to provide a high standard of care. The guidelines presented here propose recommendations for diagnosing and preventing infectious diseases among refugees under 18 years of age in Germany. The guidelines are intended to assist in optimizing vaccine protection and treatment of diseases, while taking into consideration factors such as refugees’ challenging living conditions, cultural differences, and potential language barriers.Objective and resultsUpon refugees’ arrival at first housing sites, it is recommended that a basic clinical screening (and not just a brief visual inspection) be provided in order to identify and to initiate treatment for acute medical problems and potential contagious diseases (including tuberculosis), as well as to close gaps in vaccination coverage. Documentation of clinical findings is critical to avoid redundant investigations and to optimize individual medical care. For this, an effective communication system must be established. Once refugees have been transferred into their destination community, outpatient and inpatient care providers should collaborate to bring refugees up-to-date on all STIKO recommended vaccines. The same high standard of medical care should be delivered to refugees as would be for the general population. Due to the high prevalence of multiresistant organisms (MRO) in refugees’ countries of origin, MRO screening is recommended for most patients receiving inpatient care.